Issues and challenges of waqf practice in Malaysia: a review - Mohamad I'sa Abd Jalil (Labuan Faculty of International Finance, Universiti Malaysia Sabah, 2020)
The literature of waqf is no longer foreign in the body of knowledge. Many researchers have written about waqf in various settings and disciplines. One of the waqf subjects studied was on the issues and challenges faced in practicing waqf. The objectives of this study are to review and formulate issues and challenges of waqf practices in Malaysia that have been recorded by previous researchers. Using the content analysis method, past studies have been grouped and formulated. As a result, the study found that there are seven (7) issues and challenges of waqf practices that are experienced in most places, i.e., legal issues, awareness and knowledge, lack of funds, idle assets, management inefficiencies, incomplete record data, and illegal invasion.